De Novo Crohn's Disease in Children With Ulcerative Colitis Undergoing Ileal Pouch-Anal Anastomosis: A Multicenter, Retrospective Study From the Pediatric IBD Porto Group of the ESPGHAN - Martinelli, Massimo; Romeo, Erminia; Caldaro, Tamara; Dimakou, Konstantina; Papadopoulou, Alexandra; Matar, Manar; Assa, Amit; Dipasquale, Valeria; Romano, Claudio; Aloi, Marina; Alvisi, Patrizia; Röser, Dennis; et al. (Inflammatory bowel diseases, 2024)
BACKGROUND AND AIMS: We sought to define the prevalence and to characterize possible predictive factors of Crohn's disease (CD) occurring in children with ulcerative colitis (UC) after ileal pouch-anal anastomosis (IPAA). METHODS: This was a multicenter, retrospective study including 15 centers of the Porto IBD group of the European Society for Pediatric Gastroenterology, Hepatology and Nutrition. Children with a confirmed diagnosis of UC undergoing colectomy with IPAA and a minimal follow up of 6 months were identified. The following data were collected: demographic data; endoscopic and histologic data; disease activity; laboratory exams; therapeutic history; indication for surgery, type, and timing; and IPAA functional outcomes and complications. In de novo CD cases, time of diagnosis, phenotype, location, and therapies were gathered. RESULTS: We identified 111 UC children undergoing IPAA from January 2008 to June 2018 (median age at colectomy: 13 years; age range: 1-18 years; female/male: 59/52). The median time from diagnosis to colectomy was 16 (range, 0-202) months. At the last follow-up, 40 (36%) of 111 children developed pouchitis. The criteria for de novo CD were met in 19(17.1%) of 111 children with a 25-month median (range, 3-61 months). At last follow-up, 12 (63.1%) of 19 were treated with biologics and in 5 (26.3%) of 19 children, the pouch was replaced with definitive ileostomy. In a multivariable logistic regression model, decreased preoperative body mass index z scores (odds ratio, 2.2; 95% confidence interval, 1.1-4.4; P = .01) resulted as the only variable associated with CD development. CONCLUSIONS: Children with UC undergoing IPAA carry a high risk of developing subsequent CD. De novo CD cases showed decreased preoperative body mass index z scores, identifying a poor nutritional status as a possible predictive factor.
Keywords: colectomy; Female; Infant; dítě; předškolní dítě; Pouchitis; ženské pohlaví; Colectomy; Adolescent; Proctocolectomy, Restorative; lidé; proktokolektomie rekonstrukční; pooperační komplikace; následné studie; kolektomie; Colitis, Ulcerative; Risk Factors; retrospektivní studie; ileoanal pouch anastomosis; Crohn Disease; Follow-Up Studies; Male; Postoperative Complications; children; pouchitis; kojenec; Child, Preschool; ulcerózní kolitida; de novo Crohn’s disease; rizikové faktory; Child; Crohnova nemoc; ulcerative colitis; mužské pohlaví; Retrospective Studies; mladiství; Humans